Wave Equations in Bianchi Space-Times - S. Jamal; A. H. Kara; R Narain (Journal of Applied Mathematics)
We investigate the wave equation in Bianchi type III space-time. We construct a Lagrangian of the model, calculate and classify the Noether symmetry generators, and construct corresponding conserved forms. A reduction of the underlying equations is performed to obtain invariant solutions.